Profile of SIKARYA Program Implementation to Improve Literacy of Senior High School Students - Rifqiawati, Ika; Rahayu, Siti Aini; Imaniyah, Yarfa Fadilah; Yanti, Zhahrina; Widiyastuti, Dwi Luki; Rodiah, Eneng (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
Literacy is one of the fundamental skills students must have to face the challenges of the 21st century. Literacy skills are limited to reading, writing, and creating work. One of the School Literacy Movement programs conducted at senior high school is through the implementation of the SIKARYA program. The purpose of this study was to determine how the profile of the implementation of the SIKARYA program at senior high school improved literacy and fostered students' interest in writing literary works. This study used a descriptive qualitative method to describe the SIKARYA program implemented at senior high school in depth. The results of this study obtained various information about the profile of the SIKARYA program. The SIKARYA program begins with socialization activities on Friday. Literacy activities: After socialization, students will be given material about the literary works they create. The implementation of the SIKARYA program this year is only focused on making poetry and short stories. The existence of this SIKARYA program motivates students to create literary works and fosters enthusiasm and new experiences. However, many students need more interest in making this literary work. Therefore, this program should be held again, with other strategies to attract students' interest.